2018
DOI: 10.1002/hed.25470
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of lower extremity nerve blocks for postoperative analgesia at free fibular flap donor sites

Abstract: Background We evaluated the utility of combined femoral and common peroneal nerve blocks in patients undergoing free fibular flap‐based oromandibular reconstruction. Methods Forty patients undergoing reconstructive surgeries with free fibular flaps were randomly divided into nerve block and control groups (NB and C). In group NB, both femoral and common peroneal nerve blocks with 0.33% ropivacaine were used. In group C, sham blocks were performed with saline. The primary outcomes were sufentanyl consumption du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Nine of 10 studies 16-24 (n = 1151) used an 11-point numerical scale to assess pain, including the visual analog scale (VAS) (6 studies, 16,20-24 n = 774) and the Defense & Veterans Pain Rating Scale (DVPRS) (1 study, 17 n = 65) ( Table 4 ). There was wide variation in subjective pain outcomes among the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nine of 10 studies 16-24 (n = 1151) used an 11-point numerical scale to assess pain, including the visual analog scale (VAS) (6 studies, 16,20-24 n = 774) and the Defense & Veterans Pain Rating Scale (DVPRS) (1 study, 17 n = 65) ( Table 4 ). There was wide variation in subjective pain outcomes among the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies 15–23 used morphine milligram equivalents (MMEs) to assess additional narcotic usage while Zhang et al 24 reported additional use of sufentanyl. Other significantly improved functional metrics included sedation score, antiemetic use at postoperative day (POD) 1, and time from bed to chair 16 , 24 . While hospital length of stay was reported by 4 studies, 17,19,21,24 only Smith et al 21 found a significantly decreased time for the MMA group (7.8 vs 10.6 days, P =.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is considered the most severe form of chronic pain because those who suffer from neuropathic pain may experience depression, anxiety and other harmful emotions. Drugs, such as opioids, have been demonstrated to be insufficient and cause severe side effects in neuropathic pain 2,3 . In recent years, stem cell transplantation has been reported to be a potent alternative to traditional therapies for controlling neuropathic pain 4,5 …”
Section: Introductionmentioning
confidence: 99%